Synthesis pterocarpan compounds from Erythrina crista-galli L and their action towards Plasmodium falciparum - Tjahjandarie, Tjitjik Srie (Universitas Airlangga, 2015)
Synthesis of the naturally occurred 3-acetyl sandwicensin(2) and 2,7- dibromosandwicensin(3)was carried out by acetylation and bromination reaction, respectively. The pterocarpan synthesized in this study was andwicensin(1) isolated from stem bark of Erythrina crista galli L. Their structures were established on the basis of spectroscopic evidence. Compounds 1–3 were evaluated for their antimalarial properties against Plasmodium palcifarum, showing their IC were 1.83, 34.81 and 12.9 µg/mL, respectively.